Strain assisted magnetoelectric coupling in ordered nanomagnets of CoFe2O4/SrRuO3/(Pb(Mg1/3Nb2/3)O3–PbTiO3) heterostructures. (27th July 2022) - Ahlawat, Anju; Khan, Azam Ali; Deshmukh, Pratik; Bhartiya, Sushmita; Satapathy, S; Shirolkar, Mandar M; Wang, Haiqian; Choudhary, R J
Abstract: We have explored the electric field controlled magnetization in the nanodot CoFe2 O4 /SrRuO3 /PMN-PT (CFO/SRO/PMN-PT) heterostructures. Ordered ferromagnetic CFO nanodots (∼300 nm lateral dimension) are developed on the PMN-PT substrate (ferroelectric as well as piezoelectric) using a nanostencil-mask pattering method during pulsed laser deposition. The nanostructures reveal electric field induced magnetization reversal in the single domain CFO nanodots through transfer of piezostrains from the piezoelectric PMN-PT substrate to the CFO. Further, electric field modulated spin structure of CFO nanomagnets is analyzed by using x-ray magnetic circular dichroism (XMCD). The XMCD analysis reveals cations (Fe 3+ /Co 2+ ) redistribution on the octahedral and tetrahedral site in the electric field poled CFO nanodots, establishing the strain induced magneto-electric coupling effects. The CFO/SRO/PMN-PT nanodots structure demonstrate multilevel switching of ME coupling coefficient ( α ) by applying selective positive and negative electric fields in a non-volatile manner. The retention of two stable states of α is illustrated for ∼10 6 seconds, which can be employed to store the digital data in non-volatile memory devices. Thus the voltage controlled magnetization in the nanodot structures leads a path towards the invention of energy efficient high-density memory devices.